Study of effect of binders and loading pressures on the performance of the time delay pyrotechnic compositions. Issue 4 (2nd October 2018) - Khan, Azizullah; Malik, Abdul Qadeer; Lodhi, Zulfiqar Hameed; Badshah, Gul
ABSTRACT: An experimental investigation was carried out to determine the effect of binders and loading pressures on burning performance of B/BaCrO4 and Si/PbO/Pb3 O4 delay compositions. The consolidated density and percent theoretical maximum density (%TMD) of these compositions were also studied with different binders and at multiple loading pressures. Carboxyl methyl cellulose (CMC), dextrin, and fish glue with varying wt. % were used as binders. It was observed that the burning rate of these delay compositions was inversely proportional to the binder content. The burning rate of B/BaCrO4 delay composition was 71.0 mm/s without binder. The burning rate decreased to 38.1 mm/s by adding 3.0 % fish glue. When 1.0 % CMC was added to the mixture, the burning rate decreased to 61.8 mm/s. By adding 3.0 % dextrin to the delay composition, the burning rate decreased to 38.2 mm/s. The burning rate of Si/PbO/Pb3 O4 delay mixture was 38.6 mm/s without binder. The burning of this mixture decreased to 16.4 mm/s by adding 1.0 % fish glue. The loading pressures were varied from 103 to 414 MPa. The effect of loading pressures on the burning rate of both the delay compositions was marginal. The burning rate of B/BaCrO4 delay mixture decreased with the increase in loading pressure. On contrary, the change in burning rate of Si/PbO/Pb3 O4 pyrotechnic delay composition was minimal by varying the loading pressures. Results also revealed that loading pressures of 345 and 348 MPa produced the minimum standard deviation in burning rate of B/BaCrO4 and Si/PbO/Pb3 O4 compositions. The consolidated density and %TMD of both mixtures increased by adding binders and increasing the loading pressures.